Efficacy and Safety of Apremilast in Oncological Patients with Moderate-to-Severe Plaque Psoriasis: A 5 years Retrospective Observational Study - Lanna C; Rivieccio A; Vultaggio M; Gaeta Shumak R; Bonacci FM; Artosi F; Borselli C; Costanza G; Bianchi L; Campione E (Clinical, Cosmetic and Investigational Dermatology, 2025)
Caterina Lanna,1 Antonia Rivieccio,1 Martina Vultaggio,1 Ruslana Gaeta Shumak,1 Francesco Maria Bonacci,1 Fabio Artosi,1 Cristiana Borselli,1 Gaetana Costanza,2 Luca Bianchi,1 Elena Campione1 1Dermatology Unit, Department of Systems Medicine, Università di Roma Tor Vergata, Roma, Italia; 2Virology Unit, Department of Experimental Medicine, Università di Roma Tor Vergata, Roma, ItaliaCorrespondence: Caterina Lanna, Dermatologic Unit, Department of Systems Medicine, University of Rome Tor Vergata, Viale Oxford 81, Rome, 00133, Italy, Email caterinalanna.cl@gmail.comBackground: Psoriasis and psoriatic arthritis are chronic autoimmune inflammatory conditions frequently associated with a range of comorbidities, including oncological diseases. Managing these conditions in patients with a history of cancer requires careful consideration of treatment efficacy and safety. Apremilast, an oral phosphodiesterase 4 (PDE4) inhibitor, has shown promise in the treatment of psoriasis and psoriatic arthritis. However, data on its use in oncological patients remain limited.Methods: This retrospective observational study evaluated the efficacy and safety of Apremilast in 79 patients with a history of cancer who were treated for psoriasis and/or psoriatic arthritis over a period of approximately five years. Clinical outcomes were assessed using the Psoriasis Area Severity Index (PASI), Dermatology Life Quality Index (DLQI), and Visual Analog Scale for pain (PAIN VAS) to monitor disease severity, quality of life, and articular involvement, respectively. Regular oncological assessments were conducted concurrently with Apremilast therapy to ensure patient safety and identify potential interactions.Results: Over the five-year treatment period, significant improvements were observed in PASI, DLQI, and PAIN VAS scores, indicating effective management of both dermatological and articular symptoms. Patients reported enhanced quality of life and reduced pain levels, reflecting the therapeutic benefits of Apremilast. Oncological evaluations revealed no significant adverse interactions between Apremilast and the patients’ cancer history or treatments, underscoring the drug’s safety profile in this population.Conclusion: This study highlights the efficacy and safety of Apremilast as a treatment option for psoriasis and psoriatic arthritis in oncological patients. The findings support its role in improving disease outcomes and quality of life, emphasizing the importance of personalized treatment strategies in managing complex cases involving a history of cancer. Further research is warranted to validate these results in larger patient cohorts.Keywords: psoriasis, apremilast, cancer, tumors